Fostering Junior High School Teachers’ Competence in Technology-Assisted Learning Media Development - Tusino Tusino; Titi Rokhayati; Basuki Basuki; Intan Nasihah (Universitas Muhammadiyah Purworejo, 2022)
Technology literacy and poor teaching competences are common weaknesses experienced by junior high school teachers. This is because most junior high school teachers rarely use technology-based media in developing learning materials. Lecturers of English Education Study Program, Universitas Muhammadiyah Purworejo held training on technology-assisted learning media to overcome the problems faced. The method used was covered four steps namely problem analysis, preparation, implementation, and evaluation. The training activities were carried out face to face at SMP N 22 Purworejo. A total of 36 (thirty six) teachers participated in this activity. To evaluate the training program's achievements and participant responses, close-response questionnaires and semi-structured interviews were conducted after the presentation and discussion sessions finished. The results of the interviews showed that the participants were happy and enthusiastic about participating in the training activities. This community service program is able to increase teacher competence in developing technology-based learning media. The output of this program was an article published in a national-accredited journal. Further training needs to be held by increasing the number of participants from junior and senior high school teachers.